2021
DOI: 10.1371/journal.pone.0247608
|View full text |Cite
|
Sign up to set email alerts
|

Date pits based nanomaterials for thermal insulation applications—Towards energy efficient buildings in Qatar

Abstract: Air-conditioning systems make the most significant part of energy consumption in the residential sector. There is no denying that it is essential to produce a comfortable indoor thermal environment for residents in a building. The actual goal is to achieve thermal comfort level without putting too much cost on the ecological system by trying to conserve the amount of energy consumed. An effective way to help achieve such a goal is by incorporating thermal insulation in buildings. Thermal insulations help reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Inheritance means that BIM can inherit and manage all kinds of information and data in architectural design scheme, thus facilitating later maintenance and management. For instance, to achieve the intelligent operation and management of the building, all types of characteristics, materials, equipment, and other information of the architectural design scheme are connected with the maintenance management system [19][20][21]. As a result, Fig.…”
Section: Digital Analysis Of Intelligent Building Based On Bim Techno...mentioning
confidence: 99%
“…Inheritance means that BIM can inherit and manage all kinds of information and data in architectural design scheme, thus facilitating later maintenance and management. For instance, to achieve the intelligent operation and management of the building, all types of characteristics, materials, equipment, and other information of the architectural design scheme are connected with the maintenance management system [19][20][21]. As a result, Fig.…”
Section: Digital Analysis Of Intelligent Building Based On Bim Techno...mentioning
confidence: 99%
“…On the other hand, research points to the fact that these interventions need to be part of a broader energy systems transformation, such as improving energy-efficient buildings (which are necessary for Qatar due to rising energy demand). Wastes have the potential to create positive synergies in this transition; for example, one study showed that nanomaterials based on date pits-a common food waste in the region-have a promising future in thermal insulation applications [31]. The study showed the potential of this form of insulation in building air conditioning systems (a house area of 570 m 2 ) to reduce energy consumption by 4494 kWh and carbon dioxide emissions by 1.8 tonnes every year.…”
Section: Energymentioning
confidence: 99%
“…Researchers found that nanotechnology can be a useful approach when designing resilient buildings. Resilient buildings involve all the systems integrated together such as lighting, ventilation, cooling and heating, fire system that are adapted by utilization of new technologies and addition of advanced technological systems to support the building [3]. In order to meet the needs of building users, they enable connectivity between building systems that are flexible enough to adapt easily [16].…”
Section: Introductionmentioning
confidence: 99%